PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SD - Amelia, Minda Suci; devi, Masnila (Universitas Negeri Padang, 2022)
This study aims to describe the application of the Problem Based Learning (PBL) model to improve learning outcomes on fraction material in grade IV elementary schools. This type of research is Classroom Action Research (PTK) using qualitative and quantitative approaches. The research subjects were 16 students in grade IV SD N 01 Ladang Laweh. The results showed an increase. In the first cycle, the RPP observation results were from 83.7% to 93% in the second cycle. Implementation in the aspects of teachers and students in cycle I 81.7% to 92% in cycle II. The average assessment of student learning outcomes in cycle I was 75.5% to 86.8% in cycle II.